Unfinished revolutions: The post-Soviet crisis of governance in Ukraine - Christian Fröhlich (Global Policy, 2023)
None of the three revolutions in Ukraine's modern history as an independent state has been able to both solve the problem of political representation and undertake the task of building sustainable democratic institutions. Ukraine's scores from the Berggruen Governance Index (BGI) between 2000 and 2019 show the ups and downs of state capacity and democratic accountability and illustrate not only how the revolutions remain unfinished but also how the country seems to be unable to consistently advance state formation. Ukraine has yet to find a stable developmental path. Accordingly, BGI scores show that Ukrainian politics and society continue to have difficulty advancing towards a corridor of good governance, where state capacity and accountability reinforce each other and enhance public goods provision. Instead, Ukraine is alternating between authoritarian and democratic development patterns. However, the Russian invasion that began on 24 February 2022 has contributed to uniting and consolidating Ukrainian society and politics and could considerably push the nation-building process forward.
Keywords: 320